An experimental study on the heat transfer characteristics over a radiant cooled wall exposed to mixed and forced convection driven by displacement ventilation - Camci, Muhammet; Karakoyun, Yakup; Acikgoz, Ozgen; Dalkilic, Ahmet Selim (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
An increasing demand on energy efficiency and indoor air quality exists, therefore displacement ventilation and radiant surface cooling applications are taking more attention as an investigation subject. This article presents an experimental study of mixed convection in a test chamber equipped with both radiant wall cooling and air-conditioning systems. The room is conditioned by a hydronic circuit with embedded pipes in the wall and an air jet supplied by a newly designed baseboard longitudinal slot that is apart from relevant literature. The tested radiant wall temperature is kept around 14 degrees C. Meantime; a parallel upward directional air jet is applied over the cooled wall or the opposite wall. The air jet velocity and its temperature lie within the intervals of 0.25-10 m/s and 18-28 degrees C, respectively. The natural, mixed, and forced convection heat transfer characteristics over the wall have been investigated considering the effects of radiant cooling, airflow rates, and ventilation location. The measured data are used for the derivation of mixed and forced average convective heat transfer coefficients correlations along a cooled wall. Consequently, the convection and total heat transfer coefficients over the radiant cooled wall are calculated in the ranges of 2-7.3 W/m(2)K, and 9.1-13.9 W/m(2)K, respectively.
Keywords: Convective heat transfer coefficient; Mixed convection; Forced convection; Radiant cooled wall; Displacement ventilation; ROOM; COEFFICIENTS; BUILDINGS; FLOW; AIR; Thermodynamics; Mechanics